Systems Biology 2019
DOI: 10.5772/intechopen.81535
|View full text |Cite
|
Sign up to set email alerts
|

Orf Virus: A New Class of Immunotherapy Drugs

Abstract: Orf is one of the most widespread viral diseases worldwide, usually benign and self-limiting, and mainly affects not only sheep and goats, but also various other ruminants and mammals. The causative agent, orf virus (ORFV) is a member of the genus parapoxvirus, owing to its zoonotic importance and ability to crossinfect other species sporadically. ORFV encodes virulence and immunomodulatory factors that interfere with host inflammatory effect and antiviral immune mechanisms and induces a transient and complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The inhibition of a Th1 response happens indirectly through abating the function of antigenpresenting macrophages and dendritic cells. 32 In addition, IL-10 has co-stimulatory functions on T lymphocytes associated with Th2 responses, mast cells and B cells. The molecular mass of IL-10 homologue protein is 21.7 kDa (185 amino acids sequence) making the ORFV IL-10s slightly larger than their mammalian counterparts which is ~18.6 kDa.…”
Section: Virulence Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The inhibition of a Th1 response happens indirectly through abating the function of antigenpresenting macrophages and dendritic cells. 32 In addition, IL-10 has co-stimulatory functions on T lymphocytes associated with Th2 responses, mast cells and B cells. The molecular mass of IL-10 homologue protein is 21.7 kDa (185 amino acids sequence) making the ORFV IL-10s slightly larger than their mammalian counterparts which is ~18.6 kDa.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…The amino acid sequence identity of the virus IL-10 with human IL-10 is known to be 67% in the C-terminal two thirds of the polypeptide, although the relatedness at the nucleotide level is less apparent. Curiously, the N-terminal region of the IL-10 like contains little similarity to that of mammalian IL-10 23,32 and this may help to deduce that the viral IL-10 polypeptide is larger than the mammalian counterpart.…”
Section: Virulence Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that ORFV112 deletion resulted in the attenuation of ORFV NZ2 (18). GIF is expressed in the late stage of infection and is the only known viral or cellular protein that has the dual activity of inhibiting host GM-CSF and IL-2 (14,19). The function of GIF, similar to CBP, is reported to inhibit the trafficking of monocytes into the skin to preventing inflammatory response (19).…”
Section: Introductionmentioning
confidence: 99%